Muslim al-Naysābūrī (d. 261/875) - Pavlovitch, Pavel, author.
1 online resource
Keywords: In Muslim al-Naysābūrī (d. 261/875). The skeptical traditionalist , Pavel Pavlovitch studies the life and works of Muslim b. al-Ḥajjāj al-Naysābūrī, the author of the famous collection of traditions ( ḥadīth ) al-Musnad al-ṣaḥīḥ ( The Sound Collection ), which Sunni Muslims rank as the third most authoritative source of legal and theological norms after the Qurʾān and Muḥammad b. Ismāʿīl al-Bukhārī’s Ṣaḥīḥ . Based on multiple biographical sources and Muslim’s extant works, Pavel Pavlovitch studies hitherto unexplored aspects of Muslim’s biography, elaborates on his founding contribution to the science of ḥadīth criticism, and examines the transmission history of Muslim’s Ṣaḥīḥ in unprecedented detail. The monograph includes the first systematic study of Muslim’s traditionalist theology, which played a defining role in the formation of Sunni identity.